Making gender in the intersection of the human and the divine - Shafiq, Muhammad; Donlin-Smith, Thomas (Cambridge Scholars Publishing, 2019)
This collection of essays challenges the traditional patriarchal approach to sacred literature by highlighting gender parity in sacred texts and envisioning the rise of the matriarchy in the future. The authors redefine Biblical Greek words like malakoi and arsenokoitai used in condemnation of homosexuality, and Qur'anic words like darajah and qawwamun, used for establishing patriarchy. One author reexamines the role of the Nepalese Teej festival of fasting and worship of the god Shiva in promoting male hegemony in Hinduism. Other papers examine passages like Proverbs 31:1-31, the stories of S.